Synthesis and Properties of New Endotricyclic Electron-Rich Olefins and Their Some Derivatives - Yilmaz, ULKU; Kucukbay, Hasan (Asian Journal of Chemistry, 2010)
New endotricyclic electron rich olefins (1 and 10) were synthesized and their new bisbenzimidazole derivatives were obtained from reaction of group 16 elements, PhNCS, CS2 and CH3CN. Structure of all new compounds were identified by 1H NMR, 13C NMR, FT-IR spectroscopic techniques and elemental analysis. The catalytic activity of the electronrich olefin, 1 on the benzoin condensation reaction were also investigated.